'Omic' Approaches to Study Uropathogenic Escherichia coli Virulence. Issue 9 (September 2017) - Lo, Alvin W.; Moriel, Danilo G.; Phan, Minh-Duy; Schulz, Benjamin L.; Kidd, Timothy J.; Beatson, Scott A.; Schembri, Mark A.
Abstract : Uropathogenic Escherichia coli (UPEC) is a pathogen of major significance to global human health and is strongly associated with rapidly increasing antibiotic resistance. UPEC is the primary cause of urinary tract infection (UTI), a disease that involves a complicated pathogenic pathway of extracellular and intracellular lifestyles during interaction with the host. The application of multiple 'omic' technologies, including genomics, transcriptomics, proteomics, and metabolomics, has provided enormous knowledge to our understanding of UPEC biology. Here we outline this progress and present a view for future developments using these exciting forefront technologies to fully comprehend UPEC pathogenesis in the context of infection. Trends: UPEC is the main cause of urinary tract infections. Integrated multi-omic analyses promise to provide deep insights into UPEC biology. Next-generation sequencing has enabled rapid low-cost sequencing of whole genomes, to explore the diversity of UPEC strains. The UPEC pan genome remains open, highlighting the complexity of this pathogen. Transcriptomics has identified key UPEC genes transcribed during different conditions, including laboratory growth, experimental UTI, and human UTI. Advances in mass spectrometry (MS) enable global proteome analysis. Matrix-assisted laser desorption/ionization (MALDI) imaging can be applied to dissect the spatial organization of UPEC biofilms. Surface or secreted proteins are likely to be high-value targets for identifying vaccine candidates, proteins involved in binding to host cells, and drug targets.